A new generation of ecocatalysts$^{\text{®}}$—from Invasive Alien Species to sustainable and biosourced glyceryl fatty esters - Lasbleiz, Arthur; Pelissier, Franck; Renault, Jean-Hugues; Grison, Claire M.; Legrand, Yves-Marie; Grison, Claude (Comptes Rendus. Chimie)
A new generation of ecocatalysts$^{\text{®}}$ derived from Invasive Alien Species (IAS) (Fallopia japonica and Arundo donax) was used as starting material for the preparation of novel biosourced catalysts. The preparation of these ecocatalysts$^{\text{®}}$ is a new way to support the management of IAS. These catalysts were characterized by microwave plasma atomic emission spectrometry (MP-AES) and X-ray powder diffraction (XRPD), which revealed basic properties. After calculating Pearson’s correlations to evaluate the relative importance of reaction parameters, a design of experiments (DoE) was implemented to synthesize glyceryl caprylate and oleate with a high selectivity. These molecules constitute emollients and non-ionic emulsifiers of high industrial interest. The ecocatalysts$^{\text{®}}$ were efficient and recyclable for the transesterification of methyl and ethyl fatty esters, leading to high yields (66–83%). These ecocatalysts$^{\text{®}}$ are an alternative to usual base catalysts previously reported for the transesterification of methyl caprylate, methyl oleate and ethyl caprylate with glycerol, which are often non-recyclable, not systematically selective and require questionable preparation conditions.